"Marginal Muslims": Politics and the perceptual bounds of Islamic authenticity in northern Nigeria - Casey, Conerly C. (Africa Today, 2008)
In 1999 and 2000, twelve states in northern Nigeria declared Islamic law (Shari'ah) the state criminal law for all Muslims, redefining the boundaries of identity, civility, and criminality. In the city of Kano, the implementation of Shari'ah criminal codes appealed to Muslims from all sectors of society, as democratic alternative to, and strong critique of, colonialism and the elitism and corruption of federal and state politicians. Urban ward gang members ('yan daba) agitated alongside other Muslim youths for the implementation of Shari'ah codes, yet with others deemed "marginal Muslims," became the immediate objects of preaching and surveillance by Hisbah (Shari'ah enforcers). Perceptual experiences in everyday life - whether one wore the beard of Muslim orthodoxy, or the baggy jeans and chains of Los Angeles rappers, or prayed at the tombs of Sufi saints - began to redefine and frame identity in terms of ethnic, Islamic "authenticity," morality, and neighborhood and state security. In this article, I describe the changing relations of Hisbah and 'yan daba during the 2000 implementation of Shari'ah codes in Kano, providing an analysis of the impact of the implementation itself on nonreformist residents. I show that reformist Hisbah vigilantly scrutinized Muslims living in ethnically plural spaces, Muslim ethnic minorities, and people who, by virtue of their region of origin, religion, or ethnicity, were deemed to be "marginal Muslims" or polytheists, and thus, "out of place." Reformist Hisbah considered Muslim 'yan daba, 'yan Bori (followers of Bori), nonreformist Sufis (with pro-Shari'ah Sufi critics of Hisbah), and non-Hausa Muslims, particularly Muslim Yoruba, to be political-spiritual saboteurs who dis-allowed the reenchantment of orthodoxy and its ability to function as Islamic political unity and collective memory. For 'yan daba and Hisbah, Islamic state-building became a work of ethnic, religious, and regional conflation, which through unlawful displays of masculine power conflicted with the political aspirations of moderate Muslim Hausa, and superseded personal and non-Muslim Hausa expressions of Islamic authenticity, morality, and security.
Created from Fastlane, Scopus look-up